On the core concepts of political theory: Hannah Arendt, Carl Schmitt and the ancients - Akarapattananukul, Yared (2019)
Hannah Arendt and Carl Schmitt are often thought to be diametrically opposed to one another. This thesis interrogates this view not only by focusing on the differences, but also the similarities between these two thinkers. It challenges previous studies that have overlooked the appropriation by Arendt and Schmitt of the ancient Greek and Roman traditions of political thought and practice, by arguing that looking through the lens of these traditions provides another way of the understanding Arendt’s and Schmitt’s political theories. Examining the work of Arendt and Schmitt, and their insights into the subjects of politics, sovereignty, law and war, my original contribution is twofold, in (1) comparatively elaborating the core aspects of the concepts of politics, sovereignty, law and war, with which then to (2) identify their rival appropriations of the Greek and Roman traditions underpinning political enquiry in respect of these four concepts.